Role of catecholamines in young adults with essential hypertension - Abdullah, Aszrin; Mohd Shah, Azarisman Shah; Abdul Razak, Tariq; Mohd Noor, Noriah (2011)
Background: Hypertension is a major cause of cardiovascular morbidity and mortality worldwide, and blood pressure (BP) control is poor. Adrenaline has been suggested to play a role in the pathogenesis of essential hypertension.